Sprachliche Spur der Moderne. In Gedichten um 1900: Nietzsche, Holz, George, Rilke, Morgenstern. Von Helmut Henne. Berlin: de Gruyter, 2010. 151 Seiten + 58 s / w Abbildungen. 39,95. - Elit, Stefan (Monatshefte)

Vorwort - Eke, Norbert Otto (Kathrin Röggla: das stottern des realismus: fiktion und fingiertes, ironie und kritik)

Zaal Andronikashvili: Die Erzeugung des dramatischen Textes. Ein Beitrag zur Theorie des Sujets - Eke, Norbert Otto (Germanistik)

Anna Souksengphet-Dachlauer: Text als Klangmaterial. Heiner Müllers Texte in Heiner Goebbes‘ Hörstücken - Eke, Norbert Otto (Germanistik)

Eine neue Didaktik für den Übergang? KiTa- und Grundschulkinder erforschen gemeinsam das Phänomen "Wasser" - Büker, Petra; Kordulla, Agnes; Pollmann, Achim (Die Grundschulzeitschrift, Ausgabe 250)

Brüche zwischen Schein und Sein. Zu den Chancen, Risiken und unbeabsichtigten Nebenwirkungen interkultureller Bildung für Grundschulkinder - Büker, Petra (Grundlegende Bildung ohne Brüche (Jahrbuch Grundschulforschung; Bd. 15))

"Denk-Pausen" als Impulse zur biographischen Reflexion - Konturen eines anschlussfähigen Konzeptes zur Professionalisierung der ersten und zweiten Phase der Lehrerausbildung - Büker, Petra; Nitsche, Angelika (Ästhetisch-biographische Reflexion in Lehrerbildung und Schule)

Heterogenität im Klassenzimmer. Herausforderungen für Lehrer/innenbildung und Praxis. Einführungsvortrag zum Praxistag: Interkulturelles Klassenmanagement des PLAZ sowie des Netzwerkes Lehrkräfte mit Zuwanderungsgeschichte NRW - Büker, Petra
November 2011

Das Praxissemester in der Ausbildungsregion der Universität Paderborn. Vortrag im Rahmen des Symposions: Das neue Grundschullehramt in NRW an der 20. Jahrestagung der Kommission "Grundschulforschung und Pädagogik in der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft. Universität Paderborn - Büker, Petra; Berning, Hanna
September 2011

Sichtweisen, Handlungslogiken und Belastungserleben von Grundschullehrer/innen im Umgang mit kultureller Vielfalt: Forschungsbefunde aus der Paderborner Professionsstudie Pro-LEG. Vortrag an der 20. Jahrestagung der Kommission "Grundschulforschung und Pädagogik in der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft. Universität Paderborn - Büker, Petra; Hüpping, Birgit
September 2011

Schul- und Kindergartenentwicklung als neues interdisziplinäres Forschungsfeld: Methodologische Herausforderungen am Beispiel des Paderborner Modellprojektes "Kinderbildungshaus". Vortrag an der 20. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaften. Universität Paderborn - Büker, Petra; Bührmann, Thorsten; Kordulla, Agnes
September 2011

Lernen in multiprofessionellen Teams - Integrierte Praxisforschung im Paderborner Modellprojekt "Kinderbildungshaus". Vortrag an der Jahrestagung des Nordverbunds Schulbegleitforschung an der Universität Paderborn - Büker, Petra; Kordulla, Agnes; Bunte, Nicola
September 2011

Erweiterter Gestaltungspielraum für Schulen. Welche Veränderungen beschreiben Schulleiterinnen und Schulleiter in ihrem beruflichen Selbstverständnis? - Gerick, Julia; Bloh, Bea

Wiki-Einsatz im Deutschunterricht - Mit neuen Technologien kooperatives Lernen unterstützen - Anskeit, Nadine; Eickelmann, Birgit (Unterrichtsqualität sichern – Grundschule)

EduSummIT 2011: Restructuring educational systems to move into the digital age - Davis, Niki; Eickelmann, Birgit; Patru, Mariana; Schulz-Zander, Renate; Dzvimbo, Peter

Editorial. Technology to enhance learning: Problems and Promises - Eickelmann, Birgit (Journal for Educational Research Online/Journal für Bildungsforschung Online)

Mehr Gerechtigkeit durch Zentralabitur? – Analysen einer Lehrerbefragung in NRW - Lorenz, Ramonda; Kahnert, Julia; Eickelmann, Birgit; Bos, Wilfried (Zeitschrift Schul-Management)

Das Zentralabitur in Nordrhein-Westfalen aus der Lehrerperspektive. Veränderungen für den Unterricht - Eickelmann, Birgit; Kahnert, Julia; Lorenz, Ramona; Bos, Wilfried (SchulVerwaltung NRW)

Messung computer- und informationsbezogener Kompetenzen von Schülerinnen und Schülern als Schlüsselkompetenz im 21. Jahrhundert - Eickelmann, Birgit; Bos, Wilfried (Zeitschrift Medienimpulse)

Learners' identity negotiations and beliefs about pronunciation in study abroad contexts - Müller, Mareike
This dissertation explores learner beliefs about pronunciation and their interaction with identity negotiations in a study-abroad context. Current research on studying abroad has experienced a wave of interest in learner-centered questions, gradually moving away from the narrow focus on students’ linguistic development. In particular, the effects of study abroad on learner identities have attracted attention, revealing the impact of the dispositions of individuals, as well as of interlocutors, on the language learning process. The realm of speaking, especially with regard to pronunciation research, however, has hardly benefited from this interest in the individual perspectives of sojourners. Existing studies merely measure the extent to which learners appropriate native-like accents, resulting in partly inconsistent findings with limited insight into individual learning processes and factors. I thus adopt a different focus by qualitatively investigating the interplay between sojourners’ beliefs about pronunciation and their identity constructions and negotiations. My research is based on five case studies of Canadian learners of German. Each research subject has attended a German university for one or two semesters. In applying narrative inquiry as a research tool for both the within- and cross-case analyses, I investigate participants’ accounts in interviews and e-journals, as conducted at different stages throughout the first sojourn term. Poststructuralist-constructivist conceptualizations of learner identities and beliefs guide the data analysis and interpretation. The results of the holistic and categorical content analyses give insight into the intricate relationship between beliefs about pronunciation and learners’ identity work. In their narratives, learners appear to actively use pronunciation as a tool to construct identity facets in correspondence to specific communities of practice, giving meaning to their investment in the sojourn experience. This process of mediating between different identity constructions appears to be highly complex and partially conflict-laden. The participants’ beliefs and reported learning behaviours are interconnected with their definitions of learning goals, which draw on native-speaker ideals to different extents and with varying results. These orientations are in turn related to the subjects’ degrees of critical language awareness, the latter a factor that appears to play a vital role in shaping the ability of learners to take advantage of learning opportunities. In assessing participants’ learning objectives and their readiness to reflect upon their beliefs and orientations, my study also sheds light on the influence of different learning factor constellations on intercultural learning. The results indicate that unidirectional cause-and-effect relationships cannot be drawn between learners’ beliefs about pronunciation and their abilities to approach their roles as intercultural speakers in sojourn environments. My study rather underlines the importance of illuminating individual learning experiences in their idiosyncrasies and complexities, which may lead to a stronger consideration of learners’ subjective stances in both research and teaching practice. The findings of my study suggest that the primary way that language pedagogy can thus foster the ability to engage in intercultural encounters is by helping learners to become aware of their subjective stances, their self-constructions, and the influence of those on the learning process. Therefore, developing the ability and willingness to critically reflect is crucial, especially with regard to pronunciation. In illuminating the intricate nature of learner beliefs and their influence on the learning process, my study demonstrates the importance of qualitative, emic research into the acquisition of L2 pronunciation.

Selbstkonzepte im Grundschulalter – Modelle, empirische Ergebnisse, pädagogische Konsequenzen

Lehren und Lernen im Geometrieunterricht - Hellmich, Frank (Didaktik des Unterrichts im Förderschwerpunkt Lernen. Ein Handreichung für Studium und Praxis)

Implizite Fähigkeitstheorien von Grundschulkindern vor dem Übergang auf die weiterführenden Schulen - Hellmich, Frank (Grundlegende Bildung ohne Brüche)

Entwicklung von Selbstkonzepten bei Kindern im Grundschulalter – ein Überblick - Hellmich, Frank; Günther, Frederike (Selbstkonzepte im Grundschulalter – Modelle, empirische Ergebnisse, pädagogische Konsequenzen)

Förderung der Lesekompetenz durch ein wortschatzbasiertes Lesestrategietraining bei Kindern mit Deutsch als Zweitsprache - Hellmich, Frank; Niebuhr-Siebert, Sandra (Mehrsprachigkeit: Chance oder Hürde beim Schriftspracherwerb? – empirische Befunde und Beispiele guter Praxis)

Kompetenz in der Hochschuldidaktik: Ergebnisse einer Delphi-Studie über die Zukunft der Hochschullehre - Paetz, Nadja-Verena; Ceylan, Firat; Fiehn, Janina; Schworm, Silke; Harteis, Christian

Die Auswirkungen des Bologna-Prozesses--Eine Expertise der Hochschuldidaktik - Ceylan, Firat; Fiehn, Janina; Paetz, Nadja-Verena; Schworm, Silke; Harteis, Christian (Der Bologna-Prozess aus Sicht der Hochschulforschung)

Intuitive decision making in emergency medicine: an explorative study - Harteis, Christian; Morgenthaler, Barbara; Kugler, Christine; Ittner, Karl-Peter; Roth, Gabriel; Graf, Bernhard (Handbook of intuition research)

Researching workplace learning in Europe - Gruber, Hans; Harteis, Christian (The SAGE Handbook of Workplace Learning)

EduSummIT 2011: Restructuring educational systems to move into the digital age - Davis, Niki; Eickelmann, Birgit; Patru, Mariana; Schulz-Zander, Renate; Dzvimbo, Peter

A Social Media Customer Service - Geierhos, Michaela; Lee, Yeong Su; Schuster, Jörg; Kobothanassi, Despina; Bargel, Matthias (Proceedings of the 22nd ACM Conference on Hypertext and Hypermedia)

SCM - A Simple, Modular and Flexible Customer Interaction Management System - Schuster, Jörg; Lee, Yeong Su; Kobothanassi, Despina; Bargel, Matthias; Geierhos, Michaela (International Conference on Information Society (i-Society 2011))
SCM is a simple, modular and flexible system for web monitoring and customer interaction management. In our view, its main advantages are the following: It is completely web based. It combines all technologies, data, software agents and human agents involved in the monitoring and customer interaction process. It can be used for messages written in any natural language. Although the prototype of SCM is designed for classifying and processing messages about mobile-phone related problems in social networks, SCM can easily be adapted to other text types such as discussion board posts, blogs or emails. Unlike comparable systems, SCM uses linguistic technologies to classify messages and recognize paraphrases of product names. For two reasons, product name paraphrasing plays a major role in SCM: First, product names typically have many, sometimes hundreds or thousands of intralingual paraphrases. Secondly, product names have interlingual paraphrases: The same products are often called or spelt differently in different countries and/or languages. By mapping product name variants to an international canonical form, SCM allows for answering questions like Which statements are made about this mobile phone in which languages/in which social networks/in which countries/...? The SCM product name paraphrasing engine is designed in such a way that standard variants are assigned automatically, regular variants are assigned semiautomatically and idiosyncratic variants can be added manually. With this and similar features we try to realize our philosophy of simplicity, modularity and flexibility: Whatever can be done automatically is done automatically. But manual intervention is always possible and easy and it does not conflict in any way with the automatic functions of SCM.
Keywords: Social Media Business Integration; Contact Center Application Support; Monitoring Social Conversations; Social Customer Interaction Management; Monitoring; Software Agents

Buy, Sell, or Hold? Information Extraction from Stock Analyst Reports - Lee, Yeong Su; Geierhos, Michaela (Modeling and Using Context: 7th International and Interdisciplinary Conference, CONTEXT 2011, Karlsruhe, Germany, September 26-30, 2011, Proceedings)
This paper presents a novel linguistic information extraction approach exploiting analysts’ stock ratings for statistical decision making. Over a period of one year, we gathered German stock analyst reports in order to determine market trends. Our goal is to provide business statistics over time to illustrate market trends for a user-selected company. We therefore recognize named entities within the very short stock analyst reports such as organization names (e.g. BASF, BMW, Ericsson), analyst houses (e.g. Gartner, Citigroup, Goldman Sachs), ratings (e.g. buy, sell, hold, underperform, recommended list) and price estimations by using lexicalized finite-state graphs, so-called local grammars. Then, company names and their acronyms respectively have to be cross-checked against data the analysts provide. Finally, all extracted values are compared and presented into charts with different views depending on the evaluation criteria (e.g. by time line). Thanks to this approach it will be easier and even more comfortable in the future to pay attention to analysts’ buy/sell signals without reading all their reports.

Processing Multilingual Customer Contacts via Social Media - Geierhos, Michaela; Lee, Yeong Su; Bargel, Matthias (Multilingual Resources, Multilingual Applications: Proceedings of the Conference of the German Society for Computational Linguistics and Language Technology (GSCL) 2011)
Within this paper, we will describe a new approach to customer interaction management by integrating social networking channels into existing business processes. Until now, contact center agents still read these messages and forward them to the persons in charge of customer’s in the company. But with the introduction of Web 2.0 and social networking clients are more likely to communicate with the companies via Facebook and Twitter instead of filling data in contact forms or sending e-mail requests. In order to maintain an active communication with international clients via social media, the multilingual consumer contacts have to be categorized and then automatically assigned to the corresponding business processes (e.g. technicalservice, shipping, marketing, and accounting). This allows the company to follow general trends in customer opinions on the Internet, but also record two-sided communication for customer relationship management.
Keywords: Classification of Multilingual Customer Contacts; Contact Center Application Support; Social Media Business Integration

Towards Multilingual Biographical Event Extraction - Geierhos, Michaela; Bouraoui, Jean-Leon; Watrin, Patrick (Multilingual Resources, Multilingual Applications. Proceedings of the Conference of the German Society for Computational Linguistics and Language Technology (GSCL) 2011)
Within this paper, we describe the special requirements of a semantic annotation scheme used for biographical event extraction in the framework of the Europeancollaborative research project Biographe. This annotationscheme supports interlingual search for people due to its multilingual support covering four languages such as English, German, French and Dutch.
Keywords: Biographical Event Extraction for Interlingual People Search; Semantic Annotation Scheme

Customer Interaction 2.0: Adopting Social Media as Customer Service Channel - Geierhos, Michaela (Journal of Advances in Information Technology)
Since customers first share their problems with a social networking community before directly addressing a company, social networking sites such as Facebook, Twitter, MySpace or Foursquare will be the interface between customer and company. For this reason, it is assumed that social networks will evolve into a common communication channel – not only between individuals but also between customers and companies. However, social networking has not yet been integrated into customer interaction management (CIM) tools. In general, a CIM application is used by the agents in a contact centre while communicating with the customers. Such systems handle communication across multiple different channels, such as e-mail, telephone, Instant Messaging, letter etc. What we do now is to integrate social networking into CIM applications by adding another communication channel. This allows the company to follow general trends in customer opinions on the Internet, but also record two-sided communication for customer service management and the company’s response will be delivered through the customer’s preferred social networking site.
Keywords: Social Media Business Integration; Multichannel Customer Interaction Management; Contact Centre Application Support

Adjective complementation by that-clauses: An empirical study - Mindt, Ilka

Corpus Linguistics and the Description of English - Mindt, Ilka; Lindquist, Hans (ICAME Journal 35)

Anglistische Korpuslinguistik. Eine Einführung. Grundlagen der Anglistik und Amerikanistik 33 - Mindt, Ilka; Mukherjee, Joybrato (Anglistik. International Journal of English Studies, 22, 1)

Der Kanonenbischof Christoph Bernhard von Galen und seine retrospektiven Baumaßnahmen - Seng, Eva- Maria (Total Regional. Studien zur frühneuzeitlichen Sozial- und Wirtschaftsgeschichte, FS für Frank Göttmann)

Dekor und Kirchenbau - Seng, Eva- Maria (kunst und kirche. Ökumenische Zeitschrift für zeitgenössische Kunst und Architektur)

Kulturlandschaften: Die Rückgewinnung des immateriellen Kulturerbes in die Landschaft - Seng, Eva- Maria (Demokratie – Kultur – Moderne. Perspektiven der Politischen Theorie, FS für Walter Reese-Schäfer)

„Sprache, die so tröstlich zu mir kam“. Thomas Valentin in Briefen von und an Hermann Hesse - Eke, Norbert Otto; Olasz-Eke, Dagmar

UNESCO-Weltkulturerbe und der Gedanke der Nachhaltigkeit - Seng, Eva- Maria (UNESCO heute. ZS der Deutschen UNESCO-Kommission)

Stadterweiterungen, Kirchenneubau und Pfarrgründungen im 19. Jahrhundert - Seng, Eva- Maria (Die Pfarre in der Stadt. Siedlungskern – Bürgerkirche – Urbanes Zentrum (Reihe: Städteforschung, Veröffentlichungen des Instituts für vergleichende Städtegeschichte in Münster Bd. 82))

Von Taschentüchern und anderen Dingen, oder: Die “akute Einsamkeit des Menschen”. Herta Müller und der Widerspruch - Eke, Norbert Otto (literatur für leser)

Spiegel/Bilder – Werner Fritschs Anatomie von Terror und Krieg - Eke, Norbert Otto (Terror und Form (Limbus. Australisches Jahrbuch für germanistische Literatur- und Kulturwissenschaft. Band 4))

“Gelber Mais, keine Zeit”. Herta Müllers Nach-Schrift Atemschaukel. Roman - Eke, Norbert Otto (GegenwartsLiteratur. Ein germanistisches Jahrbuch/A German Studies Yearbook 10/2011)

Wahre, unzeitige und falsche Aufklärung. Fortschreibungen einer ‘alten’ Debatte im Kontext der Französischen Revolution - Eke, Norbert Otto (“Das Leben in der Poesie”. Festschrift für Magdolna Orosz zum 60. Geburtstag)

Dem “Haufen genügt die Täuschung”. Georg Forster und das Theater - Eke, Norbert Otto (Georg-Forster-Studien)
Angaben zur Herausgeberschaft: Hg. im Auftrag der Georg-Forster-Gesellschaft von Stefan Greif und Michael Ewert Angabe zum Ort: Kassel